Literasi Matematika Siswa pada Soal PISA Konteks Kutai Ditinjau Gaya Kognitif - Amelia Indri Permatasari; Achmad Muhtadin (J-PiMat : Jurnal Pendidikan Matematika, 2026)
This study analyzes students’ mathematical literacy in solving PISA-equivalent problems based on the local cultural context of Kutai, viewed from reflective and impulsive cognitive styles. This qualitative descriptive research involved tenth-grade students of SMA Negeri 16 Samarinda. The subjects were selected purposively based on the results of a mathematical literacy test and the Matching Familiar Figures Test (MFFT). Data were collected through written tests, interviews, and documentation, and analyzed using the Miles and Huberman model. The results show that students with reflective cognitive styles tend to solve problems more systematically and carefully across the stages of formulating, employing, and interpreting, although they require more time. In contrast, impulsive students tend to respond more quickly but show lower accuracy and less structured reasoning. This study contributes to the understanding of how cognitive styles influence students’ mathematical literacy in solving PISA-equivalent contextual problems, particularly those based on local cultural contexts.Keyword: Mathematical Literacy, PISA-Equivalent Problems, Local Context, Cognitive Style